IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) DENGAN ANALISIS KEJADIAN FISIKA DALAM PEMBELAJARAN FISIKA DI SMA - Ika Nayla Rachmawati; Agus Abdul Gani; indrawati indrawati (JURNAL PEMBELAJARAN FISIKA, 2017)
This study focused on influence of Project Based Lerning Model with physics phenomena to physics instruction in SMA. The purposes of this research are: (1) to describe student’s activites in physics during learning process; (2) there is a significant influential on the learning outcomes of students who were given a Project Based Learning Model and are not given the Project Based Lerning Model. This research was an experimental study with posttest only control group design. The population in this research was X class and the samples were X IPA A and X IPA B class of SMA Unggulan BPPT Darus Sholah Jember. Data collection techniques were observation, test, interview, and documentation. Data analysis techniques were descriptive, percentage, and T-test using SPSS 22. The results of this research were the average of student’s learning activities was 83.3% (very active criteria); the sigfinikansi influential on the learning outcomes of student is 0,026 this used T-test SPSS 22. This research can be concluded: first, the average of student’s learning activities was in very active criteria. Secondly, there is a significant influential on the learning outcomes of students who were given a problem Project Based Lerning Model with physics phenomena and are not given the Model Project Based Lerning Model with physics phenomena. Keywords: Project Based Learning Model, Physics Phenomena , Student’s Activities, Learning Outcomes.